A Literature Review on Turnover and Retention of IT Employees - Aastha Tripathi, Rajlaxmi Srivastava (International Journal of Advanced Science and Technology, 2020)
This paper is a literature review in analysing the factors influencing the turnover and retention of Information Technology (IT) employees. Nowadays, the point of extreme discussion is retention of IT employees; so far a few research studies have explored the sources of employee retention issues. Present research demonstrates that specially, in the IT sector, there is paucity of literature as well as in order to make strategic policies for an organisation, there is an urge for more studies to do a systematic comparison via primary as well as secondary research for turnover and retention factors. Speculative preliminary outcomes were towards lack of recognition and admiration of employees, which are main, factors that impact turnover. The usual concerns of employees are also working hours, workload and work schedules. Additionally, organisational learning culture, career development, promotion and appreciation of contribution, working environment, reduction in workload and working hours and more flexible work patterns were important retention factors for IT employees.